2014
DOI: 10.1292/jvms.13-0539
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Avian Paramyxovirus in Migratory Waterfowls in the San-in Region of Western Japan from 2006 to 2012

Abstract: Relatively little is known about the distribution of avian paramyxoviruses (APMVs) among wild birds in Japan. Surveillance of APMV in migratory waterfowl was conducted in the San-in region of western Japan during winters of 2006 to 2012. A total of 16 avian paramyxoviruses consisting of 3 lentogenic Newcastle disease viruses (NDVs), 12 APMV-4 and 1 APMV-8 were isolated from 1,967 wild-bird fecal samples. The results show that NDV and APMV-4 are relatively widely distributed among wild waterfowl that migrate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
16
1
2
Order By: Relevance
“…There are 13 described AAvV serotypes (AAvV‐1 to ‐13) based on neuraminidase inhibition tests and hemagglutination inhibition (HI), and eight another putative serotypes have been recently isolated (AAvV‐14 to ‐21) (Jeong et al., ; Lee et al., ; Neira et al., ; Thampaisarn et al., ; Thomazelli et al., ; Yamamoto, Ito, & Ito, ). While very limited information is known about the biological and molecular characteristics of AAvV‐2 to ‐21, extensive study has been mainly conducted on AAvV‐1 (Newcastle disease virus, NDV) (Cardenas‐Garcia et al., ; Umali, Ito, Katoh, & Ito, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are 13 described AAvV serotypes (AAvV‐1 to ‐13) based on neuraminidase inhibition tests and hemagglutination inhibition (HI), and eight another putative serotypes have been recently isolated (AAvV‐14 to ‐21) (Jeong et al., ; Lee et al., ; Neira et al., ; Thampaisarn et al., ; Thomazelli et al., ; Yamamoto, Ito, & Ito, ). While very limited information is known about the biological and molecular characteristics of AAvV‐2 to ‐21, extensive study has been mainly conducted on AAvV‐1 (Newcastle disease virus, NDV) (Cardenas‐Garcia et al., ; Umali, Ito, Katoh, & Ito, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, a study showed APMV‐8 seroprevalence of 48% in commercial chicken in the United States (Warke et al., ). Recently, APMV‐8 was isolated form tundra swan from Shimane, Japan (Umali et al., ). Complete genome sequence of APMV‐8 strain Delaware and pintail/Wakuya/20/78 was found 15 342 nts long (Paldurai et al., ).…”
Section: Avian Paramyxovirus Serotype‐8 (Apmv‐8)mentioning
confidence: 99%
“…Interestingly, it has been shown that double‐crested cormorant is an important reservoir of APMVs in the wild bird population (Cross et al., ). Recently, prevalence of APMVs in migratory water fowl has been reported from Japan suggesting the species’ specific pattern of APMVs (Umali et al., ). Similarly, pigeons and mallards have been suggested to be the reservoir of APMVs (Tian et al., ; Teske et al., ; Tolf et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid interference by maternal NDV antibodies with vaccine vector performance, we created a chimeric virus ( ch NDV FHN PMV8 H5 ) by substituting the envelope glycoproteins hemagglutinin-neuraminidase (HN) and fusion protein (F) of NDV by those of APMV-8 and expressing H5 of HPAIV [ 13 ]. APMV-8 was chosen as donor of HN and F because of its apathogenicity for poultry [ 14 ], description of only weak cross-reactivity between APMV-1 and APMV-8 [ 15 , 16 ] and low prevalence [ 17 19 ]. Vaccination with this chimeric vector HPAIV-H5-vaccine resulted in efficient protection against HPAIV H5N1 infection in chickens with NDV specific maternal antibodies (MDA) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%